Determination of Chloramphenicol in Pharmaceutical Samples at Electrochemically Pretreated Glassy Carbon Electrode - Alemayehu, Tassew; Sergawie, Assefa (American Scientific Research Journal for Engineering, Technology, and Sciences, 2013)
This study focuses on the importance of electrochemical pretreatment of glassy carbon electrode (GCE) for the determination of chloramphenicol (CAP) in pharmaceutical formulations using square wave voltammeter. Electrochemical pretreatment of the electrode greatly enhanced the reduction peak current (Ip) of CAP that it shows a reduction peak current response at -0.032 V vs. Ag/AgCl at the GCE in 0.05 M acetate buffer of pH 5. Detailed experiments were carried out to establish the electrochemical property, the optimal buffer and its pH, electrode pretreatment potential, effect of concentration and square wave voltammetric parameters. Following optimization of the instrumental parameters and pH of buffer solution, the peak current response for the reduction of CAP shows an enhanced response, 5.82 times greater than the bare GCE. The method was successfully applied to three CAP containing pharmaceutical samples: CAP eye drop, CAP palmitat oral suspension and CAP as sodium succinate and the level of CAP in these samples was verified.